A Study to Assess the Diversification ecisions of a Malaysian Educational Product Company Using Resource Based View - Hoe, Chin Phin (2010)
The purpose of this study is to determine whether the COMPANY based on its existing core competency should still retain the stationery and educational related product retail business. The study was conducted through interview, observation and reviewing various documents that are available. Seven respondents were interviewed. The respondents include the senior management staff as well as other staff across the board. At the end of the study, the researcher concluded that the COMPANY should continue with the retail business of stationery and educational related product but at the same time working towards a learning organization so as to have better trained and competent staff. The COMPANY should also have a better monitoring system.